Relationship between Breastfeeding and Obesity in Childhood - Vafa, Mohammadreza; Moslehi, Nazanin; Afshari, Shirin; Hossini, Aghafatemeh; Eshraghian, Mohammadreza (Journal of Health, Population and Nutrition, 2012)
A cross-sectional study was conducted to investigate the weight status and the relationship of infant-feeding variables, birthweight and birth order with BMI in a group of Iranian children. Five hundred and eleven students of both sexes at the first grade in elementary schools (aged 7 years) were recruited randomly from all 19 educational districts of Tehran. Weights and heights of children and their mothers were measured. Data on breastfeeding (BF), formula-feeding, the timing of introduction of complementary foods (CF),birthweight, and birth order were collected from the mothers. The 2007 WHO reference value was used for determining childs weight status. Regression analysis in single and a 2-level linear regression models was used for examining the independent relationships of infant-feeding variables , birthweight and birth order with childhood BMI. The prevalence of underweight and overweight in this group of children was 7.6% and 19.7%, respectively. Total time of BF and duration of exclusive BF were not associated with childhood BMI. The timing of introduction of CF was inversely related to childhood BMI after controlling forother variables (?:-0.34; 95% CI:-0.58,-0.10). Children with an early introduction of CF had significantly higher mean BMI (p for linear trend=0.012). Birth order and birthweight were related to childhood BMI significantly. These data suggest that overweight and obesity are nutritional problems among 7 years old Teharani children. The timing of introduction of CF, birth order, and birthweight were independent predictors of childhood BMI. Neither total time of BF nor duration of exclusive breastfeeding was associated with adiposity in children. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12293 J HEALTH POPUL NUTR 2012 Sep;30(3):303-310